2017
DOI: 10.1016/j.jtumed.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of students' use of technology on their learning achievements in physiology courses at the University of Dammam

Abstract: Objective This study was conducted to investigate the possible relationship between students' use of technology and their achievements in physiology courses at five health colleges of the University of Dammam. Methods This study was conducted on 231 students studying physiology during their 2nd year at one of five health colleges (Medicine, Dental, Clinical Pharmacy, Applied Medical Sciences, and Nursing). An online survey was sent to the students regarding their use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 9 publications
5
74
0
11
Order By: Relevance
“…Similar finding was also reported by Teoh & Neo (2007). It is in line with Mayer's multimedia learning theory, which stated that the development and usage of multimedia can be used to motivate, stimulate and assist students in masterying the subject, since people processing verbal or words and visual materials or pictures separately, and a certain material can be processed at a certain time and as a result meaningful learning can be achieved when they engage in an appropriate cognitive learning process (Mayer 2002;Milkova, 2015;Al-Hariri & Al-Hattami, 2017). It means that, teachers have important roles in the student outcomes.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar finding was also reported by Teoh & Neo (2007). It is in line with Mayer's multimedia learning theory, which stated that the development and usage of multimedia can be used to motivate, stimulate and assist students in masterying the subject, since people processing verbal or words and visual materials or pictures separately, and a certain material can be processed at a certain time and as a result meaningful learning can be achieved when they engage in an appropriate cognitive learning process (Mayer 2002;Milkova, 2015;Al-Hariri & Al-Hattami, 2017). It means that, teachers have important roles in the student outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…They allow teachers a great possibility to demonstrate and visualize the subject matter more clearly and comprehensibly, as well as enabling them to prepare learning material for students to optimize their learning activities (Milkova, 2015). In line with this finding, it was also found that there was a significant relationship between students' use of multimedia learning and their achievements (Al-Hariri & Al-Hattami, 2017). It was also found that multimedia strategies effectively increased student's achievements in the primary and pre-school levels.…”
Section: Student Achievementsmentioning
confidence: 56%
“…Moreover, technology can be used to ease the effect of time constraints in the class and to complement classroom teaching with online instruction outside the class time (Lai, Yeung, & Hu, 2016). Previous research has examined the use of social media outside the classroom (Al-Hariri & Al-Hattami, 2017;Beckman, Bennett, & Lockyer, 2014;Donlan, 2014;Gosper, McKenzie, Pizzica, Malfroy, & Ashford-Rowe, 2014;Hamid, Waycott, Kurnia, & Chang, 2015) for both social and educational purposes. Most of the students in these studies are positive towards learning English online because they can access supplementary resources (Son, 2007) and feel less stressed in a "virtual community" (Goodband, Solomon, Samuels, Lawson, & Bhakta, 2012).…”
Section: Social Networking Sites In Learning and Teaching Languagesmentioning
confidence: 99%
“…Hence, many studies were found that investigate the effects of technology on students. Most researchers concluded that the use of technology in education enhances student's academic achievement, increases student's interest and generally transforms learning (Al-Hariri & Al-Hattami, 2017;Flanagan, 2008;Francis, 2017;Lynch, 2006;McCoy, 2018;Lei & Zhao, 2005;Ricks, n.d.). While the majority of the literature has shown through empirical studies that educational software plays an important role in improving the academic achievement of the student, evidence is lacking of the effectiveness of the custommade educational software assessed by means other than the use of empirical methods.…”
Section: Review Of Literaturementioning
confidence: 99%